Urban mining by flash Joule heating - Bing Deng (Nature Portfolio, 2021)
Precious metals recovery from electronics wastes, termed urban mining, is significant for a circular economy. Here, the authors reported a solvent-free and ultrafast process based on flash Joule heating to recover precious metals and remove toxic heavy metals in electronic wastes.